Monita: Aplikasi Identifikasi Gizi Buruk Balita Berbasis Mobile - Ellya Nurfarida; Fadelis Sukya; Fikha Rizky Aullia; Ratna Widyastuti (Jurnal Informatika dan Multimedia, 2025)
The promotion of the one-digit stunting program is a program of the Kediri District government; this program is needed considering that cases of stunting in toddlers with malnutrition in Kediri District are still high, at around 9.8%. In contrast to cases of malnutrition in pregnant women who have had an identification and monitoring process using an android-based application from the Ministry of Health, cases of malnutrition in toddlers in the Kediri District have not been digitized and monitored correctly. Currently, the application available for the identification of under-five malnutrition is an identification application that focuses on identification only, without being able to record under-five data, so the calculation process of each measurement must always enter the under-five data first. The application for identifying and monitoring malnutrition at Puskesmas Grogol was developed mobile to facilitate cadres in recording toddler data and adding measurements, which will be called Monita. Monita is an application developed with the Flutter programming language compatible with iOS and Android-based smartphones. Monita also provides convenience to cadres because they can access it through their smartphones without using a computer. The Monita application has features for managing regions, cadres, toddler data, reports, and supplementary feeding (PMT) for toddlers with wasting cases.